Meningkatkan Childer Wall Being Melalui Keseimbangan Aktifitas Bermain dan Belajar Pada Anak Usia Dini - Eva Dwi Yulianti; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Children's well-being is a state of well-being that encompasses physical, emotional, social, and cognitive aspects. According to John W. Santrock, early childhood development will be optimal if basic needs are met in a balanced manner. One way to achieve this is through a balance between play and learning. Play contributes to happiness, creativity, and social skills, while learning supports cognitive and language development. Lev Vygotsky emphasized that play plays a crucial role in child development. An imbalance between these two activities can lead to stress or suboptimal child development. This research uses literature studies and shows that the balance between play and learning can improve children's well-being and support children's overall development